Management of intracranial aneurysms in patients after subarachnoid haemorrhage – review - Juszkat, Robert; Nowak, Stanisław; Smól, Sławomir; Zarzecka, Anna (Przewodnik Lekarza/Guide for GPs, 2008)
Subarachnoid haemorrhage (SAH) is a common neurological emergency associated with high morbidity and mortality. It is usually caused by rupture of an intracerebral aneurysm or, less commonly, arteriovenous malformation. The purpose of treatment of intracranial aneurysms is to eliminate them from circulation. Current treatment options for intracranial aneurysms include neurosurgical methods and endovascular embolization. Until recently, endovascular treatment was restricted to patients in whom the aneurysm was unsuitable for clipping. Since the introduction of controlled detachable coils (elimination of endoleak) for endosaccular packing of aneurysms, embolization is increasingly used. The application of balloon remodelling and stent implantation allows the treatment of patients with wide-necked aneurysms.